#1**+4 **

1. First add 5 to both sides

\(x^2-11x+19+5=-5+(5)\)

So you get \(x^2-11x+24=0\)

2. Then factor

Since 3 and 8 add up to 11 and they multiply to 24. The factored version of the left side of the equation is \((x-3)(x-8)=0\)

3. Solve

You multiply each side by (x-3) or (x-8) to get \(\boxed{x=3, x=8}\)

.CalculatorUser Feb 12, 2019

#1**+4 **

Best Answer

1. First add 5 to both sides

\(x^2-11x+19+5=-5+(5)\)

So you get \(x^2-11x+24=0\)

2. Then factor

Since 3 and 8 add up to 11 and they multiply to 24. The factored version of the left side of the equation is \((x-3)(x-8)=0\)

3. Solve

You multiply each side by (x-3) or (x-8) to get \(\boxed{x=3, x=8}\)

CalculatorUser Feb 12, 2019